Switching Diplomatic Recognition Between Taiwan and China: Economic and Social Impact - Chien-Huei Wu (Routledge, 2024)
This book examines the economic and social impacts of switching diplomatic relations from Taiwan to China, and vice versa, and investigates how China achieves its foreign policy objective of dissuading Taiwan's diplomatic partners and other third parties from engaging with Taiwan. Highlighting the critical regions of Africa, Latin America and the Caribbean, and Oceania, where the diplomatic competition between Taiwan and China is fierce, the contributions to this book analyze China's promises of economic benefits, threats of economic coercion and the perils of its foreign aid to the countries in these regions in pursuit of its anti-Taiwan policy. In addition to the competition of formal diplomatic ties, it also examines how existing informal relations have influenced Taiwan's increasing interactions with Central and Eastern European countries. Finally, the book explores how Taiwan's advantage in technology sectors has successfully been translated into economic leverage for Taiwan's international diplomacy. Built upon the interdisciplinary expertise and collaborative efforts of 14 international scholars, this book will be a valuable resource to scholars and students of Taiwan studies, China studies and international relations.
Keywords: 320; Political Economy; Taiwan; China; Global Supply Chain; Foreign Aid; International Trade and Investment